Development of Mathematics E-Modules Based Open Ended Learning on Social Arithmetic Material - Marzemah, Marzemah; Sari, Dwi Ivayana (Urogram Studi Pendidikan Matematika, Universitas Ivet, 2024)
The application of conventional learning using generally circulated books without paying attention to students' conditions and traditional teaching methods is one of the triggers for students not being effective in understanding and internalizing social arithmetic concepts well. Therefore, it is necessary to develop teaching materials in the form of e-modules by implementing learning that is oriented towards student active learning, one of which is open ended learning. The aim of this research is to describe the development of mathematics e-modules based open ended learning on social arithmetic material. This research is development research using the 4-D method with the Define, Design, Develop, Disseminate stages. The test subjects for this research were class VII of Attaufiqiyah Middle School. The data collection techniques used in this research are validation, response questionnaires and tests. This research produces mathematics e-modules based open ended learning that are valid, practical and effective. It is said to be valid because based on the results of material analysis an average score of 3,915 was obtained and the design analysis results obtained an average score of 3,975. This shows that mathematics e-modules based open ended learning are valid to use. It is said to be practical because the average score for teacher and student responses is 3,982. It is said to be effective because the teacher's ability to manage learning during 2 meetings and student activities is in the very good category, and students' learning is classically complete. Keywords: development, e-module, open ended, social arithmetic.